Report of the Conference of Ministers of Agriculture of the Americas and Twentieth Regular Meeting of the Inter-American Board of Agriculture: San Jose, Costa Rica - Inter-American Board of Agriculture (IABA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2020)
Publicado en español, inglés, francés y portugués